Derajat Keterbukaan Impor Dan Derajat Konsentrasi Komoditas Kedelai Di Indonesia - Surya Brata, I Gede Chandra; Murjana Yasa, I Gusti Wayan (E-Jurnal Ekonomi Pembangunan Universitas Udayana; Vol. 4, No. 8, Agustus 2015 (pp. 873-1047), 2015)
Import a country highly dependent on Gross Domestic Product (GDP) as GDP is one source of financing imports. GDP growth is very important for the economic development of a country because it demonstrates the ability of a country to conduct international trade. This study aims to determine how much the city and DKK for soybean commodity in Indonesia. This research uses descriptive method with quantitative approach. The data used in this research is secondary data. The analysis technique used is a simple linear regression analysis techniques. Based on the results of this study showed: (1) The results of the city on average was not a significant increase, but the growth of imports of soybean in Indonesia from year to year fluctuation. To import this commodity soybean spend foreign exchange reserves amounted to 2.968 percent of the total foreign exchange reserves; (2) Based on calculations DKK showed that commodity soybean imports in Indonesia are relatively distributed from year to year. (3) Based on a simple regression analysis, the results obtained b amounted to 0,145 that indicates if the MPI increased the import of soybean in Indonesia will also increase. Based on the results of the research advice that can be given is the government should start paying attention to domestic agribusiness development so that the country will not be overly dependent on commodity imports from other countries.
Keywords: derajat keterbukaan impor, derajat konsentrasi komoditas